2014
DOI: 10.1590/s1517-83822014000400007
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the production of mycorrhizal inoculum on substrate with organic fertilizer

Abstract: The system for production of inoculum of arbuscular mycorrhizal fungi (AMF) using sand and vermiculite irrigated with nutrient solution is promising. However, organic amendments added to the substrate can stimulate sporulation of AMF and replace the nutrient solution. The aim of this study was to maximize the production of AMF (Acaulospora longula, Claroideoglomus etunicatum, Dentiscutata heterogama and Gigaspora albida) using selected organic substrates (vermicompost, coir dust and Tropstrato) together with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…These results agree with [16] who found that a block treated with biochar alone recorded the highest abundance of spores, compared to blocks treated with a combination of biochar and mycorrhiza, and attributed this to the slow adjustment of the introduced mycorrhizal species to the environment. The results of this study also agree with [21], who found that substrates treated with vermicompost produced the highest number of mycorrhizal spoeres compared with substrates treated with coir dust and Topstrato TM . They attributed this to the high levels of phosphorous in the substrate provided by vermicompost, which played an improtant role in production of AM fungi propagules.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results agree with [16] who found that a block treated with biochar alone recorded the highest abundance of spores, compared to blocks treated with a combination of biochar and mycorrhiza, and attributed this to the slow adjustment of the introduced mycorrhizal species to the environment. The results of this study also agree with [21], who found that substrates treated with vermicompost produced the highest number of mycorrhizal spoeres compared with substrates treated with coir dust and Topstrato TM . They attributed this to the high levels of phosphorous in the substrate provided by vermicompost, which played an improtant role in production of AM fungi propagules.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, genera such as Glomus and Acaulospora produce small spores and are able to survive by adapting their sporulation patterns under unfavourable conditions like aridity [22]. The results of this study also agree with [21], who found that members of the Gigasporaceae family generally produce few spores and are incapable of colonising from hyphal fragments.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[41-43, 8, 44, 45]. Addition of organic residues to the substrate is known to increase AM fungal sporulation hence leading to increased inoculum production [46][47][48][49]. Douds et al [8] successfully produced AM fungal inoculum in compost mixed with vermiculite, perlite, or horticultural potting media and observed that the propagule numbers were maximum in vermiculite based media.…”
Section: Effect Of Different Carrier Treatments On Re-inoculation/colmentioning
confidence: 99%
“…Addition of P increased both root growth and the percentage of root length colonized by AM fungi. If AM fungal isolates are produced in organic substrate with high P levels it is likely that the isolates will be more adapted to conditions of high P [51,49]. However, the overall least AM fungal interaction was observed in treatments 14 and 15.…”
Section: Effect Of Different Carrier Treatments On Re-inoculation/colmentioning
confidence: 99%